2019
DOI: 10.1038/s41467-019-10176-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EZH2 histone methyltransferase activity alleviates experimental intestinal inflammation

Abstract: Enhancer of zeste homolog 2 (EZH2)-mediated trimethylation of histone 3 lysine 27 (H3K27Me3) is critical for immune regulation. However, evidence is lacking to address the effect of EZH2 enzyme’s activity on intestinal immune responses during inflammatory bowel disease (IBD). Here we report that suppressing EZH2 activity ameliorates experimental intestinal inflammation and delayed the onset of colitis-associated cancer. In addition, we identified an increased number of functional MDSCs in the colons, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…33 A study reports that suppressive EZH2 activity improves experimental intestinal inflammation and postpones the onset of colitis-associated cancer. 35 In the meantime, targeted decline of miR-139-5p is beneficial for intestinal inflammation and colorectal cancer progress. 34 Furthermore, a recent study has revealed that overexpressed miR-139-5p reduces the inflammatory cytokines expression.…”
Section: Discussionmentioning
confidence: 99%
“…33 A study reports that suppressive EZH2 activity improves experimental intestinal inflammation and postpones the onset of colitis-associated cancer. 35 In the meantime, targeted decline of miR-139-5p is beneficial for intestinal inflammation and colorectal cancer progress. 34 Furthermore, a recent study has revealed that overexpressed miR-139-5p reduces the inflammatory cytokines expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that suppressing EZH2 activity with GSK343 ameliorated experimental intestinal inflammation and delayed the onset of colitis-associated cancer accompanied by a gradual loss of H3K27me3 expression. 204 DZNep (3-deazaneplanocin A), a potent chemical inhibitor of S-adenosylhomocysteine hydrolase that modulates chromatin accessibility through inhibition of histone methyltransferases, including EZH2, 205 can lead to a significant reduction in H3K27me3 with a marked reduction in cell proliferation and migration in CRC. Similar effects can also occur in PC, decreasing the global H3K27me3 level and subsequently causing reexpression of miR-218, thus inhibiting cell proliferation, promoting apoptosis, and inducing cell cycle arrest in PC cells.…”
Section: Clinical Application Of Histone Methylation In Digestive Canmentioning
confidence: 99%
“…Current epigenetic therapeutic approaches mainly include treatment with histone methyltransferase inhibitors (HMTis), histone deacetylase inhibitors (HDACis), and DNA methyltransferase inhibitors (DNMTis) [155]. Enhancer of zeste homolog 2 (EZH2), a gene encoding histone methyltransferase, is often overexpressed in multiple cancer types [156]. After treatment with the EZH2 inhibitor GSK343, the number of functional MDSCs increased significantly in colorectal cancer mouse models or in vitro [156].…”
Section: Radioactive Therapymentioning
confidence: 99%
“…Enhancer of zeste homolog 2 (EZH2), a gene encoding histone methyltransferase, is often overexpressed in multiple cancer types [156]. After treatment with the EZH2 inhibitor GSK343, the number of functional MDSCs increased significantly in colorectal cancer mouse models or in vitro [156]. Similarly, the use of another inhibitor, GSK126, also promoted the proliferation of MDSCs.…”
Section: Radioactive Therapymentioning
confidence: 99%